Role of the anatomic site in the association of HLA class I antigen expression level in metastases with clinical response to ipilimumab therapy in patients with melanoma - Ladányi, Andrea (J Immunother Cancer, 2020)
BACKGROUND: The clinical response to immune checkpoint inhibitors (ICIs) in only part of the treated patients, in conjunction with the potentially serious side effects associated with this type of therapy, has emphasized the need to identify biomarkers to select patients who may benefit from ICI treatment. The aim of our study was to test human leukocyte antigen (HLA) class I and II expression in melanoma metastases as potential biomarkers of response to ipilimumab and survival in patients with metastatic melanoma, since these molecules play a crucial role in the interactions of malignant cells with host’s immune system. MATERIALS AND METHODS: HLA class I and II antigen expression level in pretreatment surgical tissue samples (50 lymph node and 35 cutaneous or subcutaneous metastases) from 30 patients was analyzed by immunohistochemical staining with monoclonal antibodies. Expression levels were correlated to intratumoral density of lymphocytes expressing cluster of differentiation (CD)8, CD45RO, CD4, forkhead box P3 (FOXP3) and/or programmed cell death protein 1 (PD-1), to clinical response to treatment, and to patients’ survival. RESULTS: HLA class I antigen expression level in lymph node metastases, but not in cutaneous or subcutaneous metastases was significantly correlated to density of CD8(+) and CD45RO(+) T cells and of lymphocytes expressing PD-1, as well as to clinical response and to patients’ survival. CONCLUSIONS: Our results corroborate the role of HLA class I expression level (alone or in combination with T-cell density values) as a predictive biomarker of response to ipilimumab in patients with melanoma. In addition, our results show that this association is influenced by the anatomic site of the metastasis used to measure the HLA class I antigen expression level.